2018
DOI: 10.1007/s00431-018-3212-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of positional plagiocephaly in healthy full-term infants at 8–12 weeks of life

Abstract: Positional plagiocephaly is a common issue faced by pediatricians; our results reinforce the need of improving prevention both of sudden infant death and positional plagiocephaly, through uniform messages provided prenatally and postnatally by different health professionals. "What is Known:" •The incidence of positional plagiocephaly varies due to population studied and measuring methods. •Different factors are considered in the literature as being associated to positional plagiocephaly (infant factors, obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 42 publications
4
50
1
3
Order By: Relevance
“…The present study also found that according to international general diagnostic standards, brachycephaly was frequent among the studied term infants. The rate of brachycephaly at the age of 2-3 months is 82.0%, which is much higher than that reported by Ballardini et al (18), while the rate of plagiocephaly (44.5%) is similar to that reported by Mawji et al (46.6%) (5), suggesting that the heads of infants in Chongqing are relatively at. This relates to differences in parenting culture, customs, and esthetic preferences in different regions and nationalities.…”
Section: Discussionsupporting
confidence: 50%
“…The present study also found that according to international general diagnostic standards, brachycephaly was frequent among the studied term infants. The rate of brachycephaly at the age of 2-3 months is 82.0%, which is much higher than that reported by Ballardini et al (18), while the rate of plagiocephaly (44.5%) is similar to that reported by Mawji et al (46.6%) (5), suggesting that the heads of infants in Chongqing are relatively at. This relates to differences in parenting culture, customs, and esthetic preferences in different regions and nationalities.…”
Section: Discussionsupporting
confidence: 50%
“…DP typically develops during the first months of life, and its highest prevalence is seen in the first six months of life [9]. DP has recently been reported concerning approximately one-third of infants in the European population, although the reported prevalence varies widely according to the study population and diagnostic method used [10,11]. DP is often included in the group of congenital factors of facial asymmetry [6], even though, based on the nature of the condition and its development postnatally, it can be classified among developmental factors of facial asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The concordance between these studies is very poor for most exposures. Some recent studies have indicated that pediatricians frequently face positional plagiocephaly associated with a supine sleeping position, head position preference, and an older maternal age [2,21,42]. There is a need to prevent both sudden infant death syndrome and positional plagiocephaly by providing small suggestions to influence the everyday care environment of infants through messages to parents, prenatally and postnatally, by different health professionals [21,41].…”
Section: Discussionmentioning
confidence: 99%
“…Deformational plagiocephaly describes one of the most common head shape disorders, which is characterized by occipital flattening and asymmetric cranial vault. It has become a common reason for parents to seek a pediatrician's advice [1] Presently, its incidence in healthy full-term infants is extremely high [2]. For example, a study in Alberta (Canada) showed that the incidence of plagiocephaly in infants aged 7 to 12 weeks was estimated to be 46.60% in the 440 infants assessed.…”
Section: Introductionmentioning
confidence: 99%